Fraisinib: a calixpyrrole derivative reducing A549 cell-derived NSCLC tumor in vivo acts as a ligand of the glycine-tRNA synthase, a new molecular target in oncology - Ben Toumia, Iméne; Bachetti, Tiziana; Chekir-Ghedira, Leila; Profumo, Aldo; Ponassi, Marco; Di Domizio, Alessandro; Izzotti, Alberto; Sciacca, Salvatore; Puglisi, Caterina; Forte, Stefano; Giuffrida, Raffaella; Colarossi, Cristina; et al. (Frontiers in Pharmacology, 2024)
Lung cancer is the leading cause of death in both men and women, constituting a major public health problem worldwide. Non-small-cell lung cancerNSCLC accounts for 85-90% of all lung cancers. We propose a compound that successfully fights the tumor NSCLC growth in vivo by targeting the enzyme GARS1.We present an in-depth investigation of the mechanism through which Fraisinib (meso-(pacetamidophenyl)-calix[4]pyrrole) affects human lung adenocarcinoma A549 cell line. In a xenografted model of non-small-cell lung cancerNSCLC, Fraisinib was found to reducing tumour mass volume without affecting vital parameters or body weight of mice. Through a computational approach, we uncovered that Glycyl-tRNA synthetase (GARS1) is its molecular target. Differential proteomics analysis further confirmed that pathways regulated by Fraisinib are consistent with Glycyl-tRNA synthetase GARS1 inhibition.Fraisinib displays an excellent strong anti-tumoral potential coupled with limited toxicity on mice. Glycyl-tRNA synthetaseGARS1 has been identified and validated as a protein target of this compound. By inhibiting GARS1, Fraisinib modulates different key biological processes involved in the tumoral growth, aggressiveness and invasiveness.The overall results indicate that Fraisinib is a powerful inhibitor of non-small-cell lung cancerNSCLC growth by exerting its action on the enzyme GARS1, while displaying marginal toxicity in animal models. Together with the proven ability of this compound to cross the Blood-Brain-Barrier, we can assess that Fraisinib can kill two birds with one stone: targeting the primary tumor and its metastases "in one shot". Taken together, we suggest that inhibiting GARS1 expression and/or GARS1 enzymatic activity may be innovative molecular targets for cancer treatment.